Recycling of farm waste straw for paddy straw mushroom cultivation - Nath, Sujit K; Pradhan, L; Nayak, M P (Indian Farming, 2019)
Paddy straw mushroom production can be a better opportunity to fetch more price to the ricecultivator. Increasing popularization of threshers has made difficult to find out uncrumbled strawsfor paddy straw mushroom cultivationm. On the other side, threshed straws are seen keptunderutilized and also wasted in the farmyard. KVK, Keonjhar has standardizd the technique touse the wasted threshed straw for production of paddy straw mushroom for the farmers of Odisha.It will directly benefit lakhs of rice farmers of the nation and lead them for prosperity through ricefarming and self employment through mushroom production.